Preoperative biliary drainage in patients with hilar cholangiocarcinoma undergoing major hepatectomy - Xiong, Jun-Jie; Nunes, Quentin M; Huang, Wei; Pathak, Samir; Wei, Ai-Lin; Tan, Chun-Lu; Liu, Xu-Bao (World journal of gastroenterology : WJG, 2013)
To investigate the effect of preoperative biliary drainage (PBD) in jaundiced patients with hilar cholangiocarcinoma (HCCA) undergoing major liver resections. An observational study was carried out by reviewing a prospectively maintained database of HCCA patients who underwent major liver resection for curative therapy from January 2002 to December 2012. Patients were divided into two groups based on whether PBD was performed: a drained group and an undrained group. Patient baseline characteristics, preoperative factors, perioperative and short-term postoperative outcomes were compared between the two groups. Risk factors for postoperative complications were also analyzed by logistic regression test with calculating OR and 95%CI. In total, 78 jaundiced patients with HCCA underwent major liver resection: 32 had PBD prior to operation while 46 did not have PBD. The two groups were comparable with respect to age, sex, body mass index and co-morbidities. Furthermore, there was no significant difference in the total bilirubin (TBIL) levels between the drained group and the undrained group at admission (294.2 ± 135.7 vs 254.0 ± 63.5, P = 0.126). PBD significantly improved liver function, reducing not only the bilirubin levels but also other liver enzymes. The preoperative TBIL level was significantly lower in the drained group as compared to the undrained group (108.1 ± 60.6 vs 265.7 ± 69.1, P = 0.000). The rate of overall postoperative complications (53.1% vs 58.7%, P = 0.626), reoperation rate (6.3% vs 6.5%, P = 1.000), postoperative hospital stay (16.5 vs 15.0, P = 0.221) and mortality (9.4% vs 4.3%, P = 0.673) were similar between the two groups. In addition, there was no significant difference in infectious complications (40.6% vs 23.9%, P = 0.116) and noninfectious complications (31.3% vs 47.8%, P = 0.143) between the two groups. Univariate and multivariate analyses revealed that preoperative TBIL > 170 μmol/L (OR = 13.690, 95%CI: 1.275-147.028, P = 0.031), Bismuth-Corlette classification (OR = 0.013, 95%CI: 0.001-0.166, P = 0.001) and extended liver resection (OR = 14.010, 95%CI: 1.130-173.646, P = 0.040) were independent risk factors for postoperative complications. Overall postoperative morbidity and mortality rates after major liver resection are not improved by PBD in HCCA patients with jaundice. Preoperative TBIL > 170 μmol/L, Bismuth-Corlette classification and extended liver resection are independent risk factors linked to postoperative complications.